2004
DOI: 10.1046/j.1399-6576.2003.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Practices of anaesthesiologists with regard to withholding and withdrawal of life support from the critically ill in Turkey

Abstract: While a number of similarities were found between Turkish anaesthesiologists and those from other countries, some specific differences could be identified, particularly related to consensus decision-making and sharing information with other providers and the value of Ethics Committees in the decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 23 publications
2
35
0
2
Order By: Relevance
“…Öyle ki Hong Kong, Pakistan, Filipinler ve Singapur'dan hemen bütün katılımcılar DNR uygulasalar da, Çin ve İran'daki hekimlerin yaklaşık yarısı bunu uygulamaktadır. Ülkemizde bu konuda Anesteziyolojistler üzerinde yapılmış bir çalışmada hekimlerin %65,9'u DNR uygulaması yaptıklarını, bu süreçte sıklıkla meslektaşlarına danış-tıklarını (%82,7) belirtirken %14,4'ü aileye, %1,7'si ise Etik Komiteye sorduklarını belirtmişlerdir (5). Her hastanede Etik Komite olmasına rağmen bu kadar düşük oranda danışılmanın nedeni ülkemizde "yaşam sonu" tıbbının yasal bir altyapısının olmamasıdır.…”
Section: Discussionunclassified
“…Öyle ki Hong Kong, Pakistan, Filipinler ve Singapur'dan hemen bütün katılımcılar DNR uygulasalar da, Çin ve İran'daki hekimlerin yaklaşık yarısı bunu uygulamaktadır. Ülkemizde bu konuda Anesteziyolojistler üzerinde yapılmış bir çalışmada hekimlerin %65,9'u DNR uygulaması yaptıklarını, bu süreçte sıklıkla meslektaşlarına danış-tıklarını (%82,7) belirtirken %14,4'ü aileye, %1,7'si ise Etik Komiteye sorduklarını belirtmişlerdir (5). Her hastanede Etik Komite olmasına rağmen bu kadar düşük oranda danışılmanın nedeni ülkemizde "yaşam sonu" tıbbının yasal bir altyapısının olmamasıdır.…”
Section: Discussionunclassified
“…A survey reported that among 439 Turkish anaesthesiologists (who were Muslims in 90% of the cases), 66% had initiated a written or oral DNR order at least once [14]. In one Lebanese ICU, 46% of all deaths were associated with one kind of EOL decision, mainly withholding life-sustaining treatments (86%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, Islam accepts the principle of putting an end to futile treatments, allowing death to take its natural course, while overzealous treatment is reprehensible if the physicians are certain about the inevitability of death [11,12]. However, only inferences about Muslim physicians' practice regarding EOL decisions can be made so far [13][14][15].…”
mentioning
confidence: 99%
“…Life-support technology has advanced, so that it is now possible to maintain vital organ function, despite the realization that a return of the patient to reasonable health and an acceptable quality of life are no longer possible. When a return to reasonable health is no longer possible, it has become common clinical practice worldwide for ICU staff to limit life-sustaining treatments (LSTs) by withholding (WH) or withdrawing (WD) LSTs [4][5][6][7][8][9][10][11][12]. There are, however large differences in the practice of WH/WD in different parts of the world as evidenced by responses to several surveys that have explored physicians' practice and ethical views on the subject [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%